Find the general solution of the given second-order differential equation. y'' + 4y' + 4y = 0
Solution:
Given, the differential equation is y’’ + 4y’ + 4y = 0
We have to find the solution of the equation.
The differential equation can be rewritten as (D2 + 4D + 4)y = 0
Where, D = d/dx
Auxiliary equation is m2 + 4m + 4 = 0
Using quadratic formula,
\(x=\frac{-b\pm \sqrt{b^{2}-4ac}}{2a}\)
Here, a = 1, b = 4, c = 4
\(\\x=\frac{-4\pm \sqrt{(4)^{2}-4(1)(4)}}{2(1)}\\x=\frac{-4\pm \sqrt{(16-16}}{2}\\x=\frac{-4}{2}\)
x = -2
Since, there is only one root, the general solution is of the form
\(y(x)=C_{1}e^{k_{1}x}+C_{2}xe^{k_{1}x}\)
Her, k1 = -2
\(y(x)=C_{1}e^{(-2)x}+C_{2}xe^{(-2)x}\)
Taking out common term,
\(y(x)=(C_{1}+C_{2}x)e^{-2x}\)
Therefore, \(y(x)=(C_{1}+C_{2}x)e^{-2x}\) is the general solution.
Find the general solution of the given second-order differential equation. y'' + 4y' + 4y = 0
Summary:
The general solution of the given second-order differential equation. y'' + 4y' + 4y = 0 is \(y(x)=(C_{1}+C_{2}x)e^{-2x}\).
visual curriculum